Educação e formação estética: entre a arte e a política - Oliveira, Lucília Chaves de (2018)
This dissertation proposes to investigate the formative processes in the educational scope, with a view to understanding how aesthetics may or may not contribute to teacher training and performance. The purpose is to think about the relations between aesthetics and human formation as a socio-historical and cultural process in the specificity of the contemporary context and the challenges that arise from it. It seeks to analyze the interrelation of the sensible with the intelligible, considering them constituent elements of the human being in its totality. It also deals with art in its political potential, as a questioning element that favors reflection on the dominations imposed by the capitalist system, which imposes aesthetic standards aiming at the maintenance of powers and privileges of class, race and gender. Aesthetics is analyzed from a perspective of resistance with an emphasis on the feminist movement, taking as reference the contemporary feminine artistic movement. In this sense, education is understood as a non-neutral political field, a space of disputes, negotiations and interests, supported by epistemological conceptions which, if considered in their critical perspectives, can deconstruct sexist educational practices, constructing practices that consider the human in all its diversity.